What does it take to implement open innovation? Towards an integrated capability framework. Issue 1 (3rd February 2017) - Hosseini, Sabiölla; Kees, Alexandra; Manderscheid, Jonas; Röglinger, Maximilian; Rosemann, Michael
Abstract : Purpose: In a world of ever-changing corporate environments and reduced product life cycles, most organizations cannot afford anymore to innovate on their own. Hence, they open their innovation processes to incorporate knowledge of external sources and to increase their innovation potential. As the shift toward open innovation (OI) is difficult and makes many initiatives fail, the question arises which capabilities organizations should develop to successfully implement OI. As the literature encompasses mature but isolated streams on OI capabilities, there is a need for an integrated capability framework. The paper aims to discuss these issues. Design/methodology/approach: This paper proposes the open innovation capability framework (OICF) that compiles and structures capabilities relevant for implementing OI. The OICF covers the outside-in and coupled processes of OI. To integrate multiple streams of the OI literature, the OICF builds on a structured literature review. The OICF was also validated in a two-step review process with OI experts from academia and industry. Findings: The OICF comprises 23 capability areas grouped along the factors such as strategic alignment, governance, methods, information technology, people, and culture. To analyze the existing body of knowledge on OI capabilities, the authors compare the OICF with other OI-related capability frameworks and compile a heatmap based on the results of the literature review. The authors also discuss the experts' feedback on individual factors of the OICF as well as on interdependencies among these factors. Practical implications: The OICF provides practitioners with a structured overview of the capabilities to consider when implementing OI. Based on the OICF, practitioners can define the scope of their OI initiatives. They can use the OICF as a foundation for prioritizing, selecting, and operationalizing capability areas as well as for deriving implementation roadmaps. Originality/value: The OICF is the first framework to take a holistic perspective on OI capabilities. It integrates mature but isolated research streams of OI. It helps practitioners define the scope of OI initiatives and academics gain insights into the current state of the art on OI capabilities.